Implementation and Evaluation of a Web-Based ZIS Fund Management Information System at UPZIS of Politeknik Negeri Lhokseumawe - Muhammad Azzahari; Khairil Fata; Rika Rahmawati; Muhammad Nasir; Rozaliana Rozaliana; Cut Mutia Safrida Ulfa (Journal of Artificial Intelligence and Software Engineering, 2026)
Digital transformation in the management of zakat, infaq, and shadaqah (ZIS) has become an essential requirement to improve transparency, accountability, and service efficiency in social and religious fund management institutions. At the Zakat, Infaq, and Shadaqah Collection Unit (UPZIS) of PNL, the management of donor and beneficiary data was previously conducted manually, leading to recording errors, reporting delays, and difficulties in monitoring fund distribution. This study aims to implement and evaluate a web-based ZIS fund management information system to support a more effective and integrated data management process. The research employed the Prototype method, which includes requirements analysis, system design, prototype development, testing, and system evaluation stages. The developed system provides features for managing donor data, beneficiary data, fund receipt and distribution transactions, as well as digital and real-time reporting. System evaluation was conducted through functionality testing and user testing to assess the usability and effectiveness of the system. The results indicate that the system improves data management efficiency, accelerates reporting processes, and enhances transparency in ZIS fund distribution within the campus environment.